The Sustainable Development Model Based on Zakat According to Antonio Gramsci and Hassan Hanafi Perspectives - Nikmatul Masruroh; Gita Pamudji; Muhammad Darul Ulum (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Zakat management in Indonesia faces significant challenges despite its potential as a powerful instrument for poverty alleviation and sustainable development. Low community awareness in channeling zakat through official institutions, coupled with the persistence of traditional distribution models such as personal giving and 'kyai kampung' practices, has hindered the optimal utilization of zakat as a socio-economic tool. This study aims to describe zakat management patterns in Indonesia, map sustainable development models through zakat management, and analyze these models from the perspectives of Antonio Gramsci and Hassan Hanafi. Method: This research employs a literature review approach with secondary data sources. Data analysis utilizes Gramsci's hegemony theory and Hassan Hanafi's At-Turats wa At-Tajdid framework to critically examine zakat management practices and their potential for sustainable development. Results: The findings reveal three key results. First, zakat management by official institutions remains suboptimal due to low public awareness, with personal distribution and local religious leader models still prevailing. Second, sustainable development models have not positioned zakat as a primary instrument, remaining largely conceptual rather than fully implemented. Third, Gramsci's hegemony theory suggests that sustainable development through zakat requires cultural and ideological struggle to transform zakat into a societal way of life, while Hanafi's reform framework emphasizes the need to reinterpret zakat's role beyond religious obligation toward economic self-reliance. Conclusion: Zakat-based sustainable development must be pursued through cultural and ideological transformation, positioning zakat not merely as a religious duty but as a strategic social and economic instrument for building a just and sustainable society.